New perspective on the recent challenges of regional environmental management plans under the background of deep-sea mining: from Northwest Pacific to global - Zhou, Wencui; Li, Tianzhao; Qi, Xuewei (Frontiers in Marine Science, 2024)
With the utilization of the mineral resources of the international seabed area entering a new phase of exploitation, the international community's concern for the protection of the marine environment in the international seabed area has also reached an unprecedented level. Regional Environmental Management Plans (REMPs), formulated by the International Seabed Authority (ISA), are considered as an important component of marine environmental protection in the deep seabed. However, REMPs are faced with challenges in practice under the background of deep-sea mining. In this work, we review the historical evolution of REMP, sort out the challenges faced by REMP from NWP to global and provide our suggestions to solve these issues. Specifically, the difficulties in the Northwest Pacific (NWP) REMP are mainly located in the lack of environmental scientific data. Meanwhile, from a global perspective, besides difficulties in local region, such as NWP, REMPs are facing more challenges, such as the arguments about the legal force of REMPs, conflicts between REMPs and the BBNJ Agreement, as well as absence of regulations for balancing exploitation and conservation. Focus on these challenges, suggestions are proposed including using the ISA to coordinate the application between REMPs and BBNJ Agreement and using the principle of scientific evidence to improve the regulations of REMPs. This work not only introduces a new insight for improving the framework system for the protection of the marine environment in the international seabed area, but also provides a reference for the solution to new challenges in the field of marine environmental protection.